A new antagonist of caenorhabditis elegans glutamate-activated chloride channels with anthelmintic activity - Castro, Maria Julia (2020)
Nematode parasitosis causes significant mortality and morbidity in humans andconsiderable losses in livestock and domestic animals. The acquisition of resistanceto current anthelmintic drugs has prompted the search for new compounds for whichthe free-living nematode Caenorhabditis elegans has emerged as a valuable platform.We have previously synthetized a small library of oxygenated tricyclic compoundsand determined that dibenzo[b,e]oxepin-11(6H)-one (doxepinone) inhibits C. elegansmotility. Because doxepinone shows potential anthelmintic activity, we explored itsbehavioral effects and deciphered its target site and mechanism of action on C. elegans.Doxepinone reduces swimming rate, induces paralysis, and decreases the rate ofpharyngeal pumping required for feeding, indicating a marked anthelmintic activity. Toidentify the main drug targets, we performed an in vivo screening of selected strainscarrying mutations in Cys-loop receptors involved in worm locomotion for determiningresistance to doxepinone effects. A mutant strain that lacks subunit genes of theinvertebrate glutamate-gated chloride channels (GluCl), which are targets of the widelyused antiparasitic ivermectin (IVM), is resistant to doxepinone effects. To unravel themolecular mechanism, we measured whole-cell currents from GluCla1/b receptorsexpressed in mammalian cells. Glutamate elicits macroscopic currents whereas noresponses are elicited by doxepinone, indicating that it is not an agonist of GluCls.Preincubation of the cell with doxepinone produces a statistically significant decrease ofthe decay time constant and net charge of glutamate-elicited currents, indicating that itinhibits GluCls, which contrasts to IVM molecular actions. Thus, we identify doxepinoneas an attractive scaffold with promising anthelmintic activity and propose the inhibitionof GluCls as a potential anthelmintic mechanism of action.